To factor the polynomial \( 16x^8 - 49x^2 \), we can recognize that it is a difference of squares. The expression can be rewritten in the form \( a^2 - b^2 \), where:
- \( a^2 = 16x^8 \) and thus \( a = 4x^4 \)
- \( b^2 = 49x^2 \) and thus \( b = 7x \)
Using the difference of squares formula \( a^2 - b^2 = (a - b)(a + b) \), we can factor the polynomial as follows:
\[ 16x^8 - 49x^2 = (4x^4 - 7x)(4x^4 + 7x) \]
Therefore, the correct response is that the pattern \( (a - b)(a + b) = a^2 - b^2 \) can be used to factor \( 16x^8 - 49x^2 \).